Adherence with bladder irrigation following augmentation. Issue 1 (February 2020) - Peycelon, Matthieu; Szymanski, Konrad M.; Francesca Monn, M.; Salama, Amr K.; Risk, Hillary; Cain, Mark P.; Misseri, Rosalie
Summary: Background: Patients with bladder augmentation (BA) are routinely counseled to irrigate their bladders daily. However, reports of adherence with this regimen are lacking. Objective: To evaluate adherence to a bladder irrigation protocol and identify risk factors associated with adherence among adults with spina bifida (SB) and BA. Study design: Adults with SB after BA followed in a multidisciplinary clinic were identified (2017–2019). All patients or caregivers were taught the importance of and the technique for the bladder irrigation protocol prior to and after BA. Patient demographics (age, gender, ambulatory status, and presence of a caregiver in clinics) and surgical details (type of BA, age at surgery, length of follow-up, presence of a catheterizable channel, position of stoma, bladder neck surgery, presence of Malone antegrade colonic enema or ventriculo-peritoneal shunt, and number of stone surgeries) were obtained from the medical record. Patients reported other variables in a standardized clinic questionnaire. Answers were confirmed by health care providers. The variables included who performs clean intermittent catheterization (CIC), size of catheter, frequency of CIC, use of overnight catheterization, difficulties with CIC, number of UTIs, and continence per urethra and per catheterizable channel. Adherence to bladder irrigation was also assessed in the questionnaire. ‛Strict adherence' was defined as bladder irrigation performed ≥6 times/week with ≥120 mL of saline. For statistical analysis, a more lenient definition of ‛higher adherence' was used: bladder irrigation ≥2 times/week with at least 60 mL. ‛Lower adherence' was defined as ≤1 time/week or with less than 60 mL. Factors associated with ‛higher adherence' were assessed with non-parametric tests (Bonferroni-corrected p -value: 0.002). Results: Adherence was assessed in 87 eligible patients (60.9% females; mean age of 28.8 ± 8.2 years). No patient (0.0%) reported ‛strict adherence', and 62 and 25 patients (71.3% and 28.7%) reported ‛higher' and ‛lower' adherence' to bladder irrigation, respectively. Nine patients (10.3%) in the ‛lower adherence' group did not irrigate at all. No variables were statistically significant on univariate analysis, including previous bladder stone surgery or having a channel ( p ≥ 0.01). On exploratory analysis, higher adherence was only associated with self-catheterizations versus those performed by caregivers (76.7% vs 33.3%, p = 0.01). Conclusions: Adherence to a bladder irrigation protocol in adults with SB and BA is poor. A history of bladder stones requiring surgery and the presence of a catheterizable channel do not appear to affect adherence. It remains unclear why some patients are more likely than others to irrigate their bladders. Future work will focus on methods to improve adherence. Summary Table Adherence prevalence. Summary N = 87 Strict adherence (≥6/wk. + ≥120 mL) 0 (0.0%) Some adherence (≥2–5/wk. and ≥60 mL) 62 (71.3%) Poor adherence (≤1/wk. or ≤60 mL) 16 (18.4%) No adherence (no irrigation at all) 9 (10.3%) N = 87 Higher adherence (2 or more times/wk. with 60 mL or more each time) 62 (71.3%) Lower adherence (1 time/wk. or less with 60 mL or less each time) 25 (28.7%) mL, milliliter; wk., week.